1998
DOI: 10.18474/0749-8004-33.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Pyrethroid Resistance in Bollworm (Lepidoptera: Noctuidae) Moths in Missouri, 1988 to 1994

Abstract: From 1988 to 1994, adult vial bioassays were conducted on bollworms, Helicoverpa zea (Boddie), collected from pheromone traps in Missouri to determine their susceptibility to pyrethroids. Although most moths were susceptible to cypermethrin, many assays contained individuals that survived concentrations of 5 and 10 μg per vial. The number of individuals that survived these concentrations increased each of the first 3 yrs, and then fluctuated from year to year. In some cases, moths with increased tolerance to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…6). Routine reports of pyrethroid resistance in bollworm are common in the literature [94][95][96][97][98][99][100][101] and may follow a pattern of highly variable response over time, perhaps a pattern similar to that of bollworm response to Bt toxins (Fig. 7).…”
Section: Target Lepidoptera Non-target Lepidoptera Non-target Non-lepmentioning
confidence: 99%
“…6). Routine reports of pyrethroid resistance in bollworm are common in the literature [94][95][96][97][98][99][100][101] and may follow a pattern of highly variable response over time, perhaps a pattern similar to that of bollworm response to Bt toxins (Fig. 7).…”
Section: Target Lepidoptera Non-target Lepidoptera Non-target Non-lepmentioning
confidence: 99%
“…Immigration of resistant adults, however, can also lead to resistance evolution (Caprio andTabashnik 1992, Croft andDunley 1993). Sorenson et al (1998) reported increased pyrethroid tolerance in Missouri bollworms in regions where no pyrethroids were used, citing immigration of resistant moths as the causal factor.…”
mentioning
confidence: 99%